The efficacy of lorlatinib in a lung adenocarcinoma patient with a novel ALK G1202L mutation: a case report. Issue 1 (2nd January 2021) - Meng, Zhaoting; Li, Ting; Wang, Pei; Lizaso, Analyn; Huang, Dingzhi
ABSTRACT: Acquired mutations in anaplastic lymphoma kinase ( ALK ) gene have been implicated as the major resistance mechanism to ALK inhibitors; however, information on the treatment options after acquiring novel ALK secondary mutations is limited. Herein, we report the efficacy of lorlatinib upon the detection of a novel ALK G1202L after progression on brigatinib. Our patient was a 30-year-old man with ALK -rearranged advanced lung adenocarcinoma. He had a partial clinical response to crizotinib lasting 11 months. Brigatinib was then administered for 12.8 months with stable disease as the best response. Sequencing at progression revealed the retention of EML4-ALK fusion and the emergence of a novel ALK G1202L mutation. With no standard treatment available, lorlatinib was administered, which achieved disease control for 9 months. Our report reveals the efficacy of lorlatinib in targeting ALK G1202L and can serve as an option for the clinical management of patients with ALK -rearranged lung adenocarcinoma after acquiring G1202L-mediated resistance from prior ALK inhibitor therapy. Furthermore, we also demonstrate the sequential use of crizotinib, brigatinib, and lorlatinib in a patient with advanced ALK -rearranged lung adenocarcinoma with an overall progression-free survival of 33.3 months for the sequential ALK inhibitor regimens. His overall survival was 41.5 months inclusive of all regimens.